Light and Electron-Microscopic Studies on the Paraepiglottic Tonsil of the Buffalo (Bubalus bubalis) - Girgiri, Ibrahim Alhaji; Kumar, Pawan (Journal of Buffalo Science, 2021)
The paraepiglottic tonsil present on either side of the base of the epiglottis constitutes a small portion of the mucosa-associated lymphoid tissue. The present study was conducted on the paraepiglottic tonsils of 12 adult buffaloes of the local mixed breed to explore its basic histomorphological, histochemical, and ultrastructural characteristics and to compare with other tonsils of the oral region to ascribe immunological function. The tonsil mucosa was lined by partly stratified squamous keratinised epithelium towards the outer surface and a stratified squamous non-keratinised epithelium towards the shallow crypts. The non-keratinised epithelium modified into reticular type due to infiltration of underlying lymphoid tissue was characterised by the predominance of the lymphoid cells, interrupting basement membrane and indistinct strata. The reticular epithelium at places presented a spongy appearance. The loose irregular connective tissue of propria-submucosa was mainly comprised of glandular and lymphoid tissue. The lymphoid tissue was mainly in the form of isolated lymphocytes, diffuse aggregations, and lymphoid follicles. The inter-follicular areas showed the presence of high endothelial venules. The sero-mucous type of glandular acini presented a strong reaction for glycogen, acidic mucosubstances, weakly sulfated mucosubstances, mucin, and the presence of more than 4% cysteine in their secretions. The tonsils under scanning electron microscopy presented an undulating appearance due to the presence of crest and folds. Higher magnification revealed squamous cells having various patterns and arrangements of microplicae. Small pits visualised on the mucosal surface represented openings of the glandular ducts. The cells towards the lumen of some glandular ducts appeared whorl-like where typical microplicae were absent. The transmission electron microscopy of different strata of different types of epithelia showed varying cell organelles, especially the mitochondria, endoplasmic reticulum, Golgi apparatus, and few filaments. The structural features of the tonsil were similar to those of other oral tonsils and suggested their immunological role, which might be of importance to local immunity.